Mempelajari Koneksitas Antara Charf Jarr dan Fi’il untuk Meningkatkan Penguasaan Kosakata Bahasa Arab - Iqbal, Moch (Maharaat: Jurnal Pendidikan Bahasa Arab, 2018)
Studying charf jarr was not just focused on understanding its function which was as a tool to stop the noun after it. But more than that, its existence after verb gave new meaning to the verb. Therefore, one verb did not only have one meaning, but it had many different meanings. There were several connection patterns between verb and charf jarr that came after it, among them were tanâwub churûf, tarâduf, tadhâd, ta'diyah, and verb connections with more than one charf jarr. From some of these connections could generate new meanings for the verb. Given this diversity of meaning, it would enrich our Arabic vocabulary. Therefore, learning charf jarr connected to previous verb would make it easier for us to increase the mastery of Arabic vocabulary.